PENINGKATAN SIKAP ILMIAH PADA PEMBELAJARAN FISIKA SISWA SMK LABOR BINAAN FKIP UR KELAS XI DENGAN MENGGUNAKAN PENDEKATAN ACCELERATED LEARNING TYPE MASTER - Huzaimah Auda; Muhammad Nasir; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The low level of scientific attitude possessed by some students also to low learning outcomes obtained by these students. This study aims to determine the improvement of students scientific attitude on physics learning at SMK Labor Binaan FKIP UR Pekanbaru by using accelerated learning type MASTER. This research Quasi Experimental Desaign with experimental class XI TKJ 17 men and 5 women, control class XI RPL 19 men and 7 women. This data is collected by giving a scientific attitude questionnaire where there are 4 indicators of scientific attitude studied are: 1. Curiosity attitude, 2. Critical thinking attitude, 3. Open thinking attitude, 4. Attitude honest. Data were analyzed descriptively. The average result of the pretest experimental class score was 70.70 and the posttest result was 79.33. Increased with the medium N-Gain category. While the average score of pretest control class score of 72.20 and posttest result of 75.34. Increased with low N-Gain category. Test t on pretest obtained tcount <ttabel that is -0.72 <2.01, can be interpreted there is no difference of scientific attitude of initial experiment class and control, t test on posttest got tcount> ttable that is 3.61> 2.01, can be interpreted there is a difference in the final scientific attitude of experimental class and control. Based on the results obtained, it can be concluded that there is a significant influence of model accelerated learning type MASTER on students scientific attitude on temperature and heat materials in class XI SMK Labor Binaan FKIP UR Pekanbaru Keywords: Model Accelerated Learning Type MASTER, scientific attitude, temperature and heat material.